Analysis of Information Service Pricing Scheme Model Based on Customer Self-Selection - Indrawati; Fitri Maya Puspita; Resmadona; Evi Yuliza; Oki Dwipurwani; Sisca Octarina (Science and Technology Indonesia, 2021)
This study attempts to analyze pricing schemes with monitoring cost and marginal cost for perfect substitute and quasi-linear utility functions for achieving Internet service Provider (ISP) in gaining benefit. Two types of customers analyzed, namely customers who are heterogeneous (both high-end and low-end) as well as heterogeneous customers (high-demand and low-demand) based on Flat-fee, usage-based, and two-part tariff are the three types of pricing methods employed. The results show that usage-based pricing schemes gain maximum profit optimal for heterogeneous customers (high-end and low-end), while for heterogeneous customers (high-demand and low-demand) type of pricing scheme two-part tariff obtains maximum profit optimal. The results of this study are more directed to the lemma of the perfect substitute utility function which compares the lemma of heterogeneous customers. This model was solved using LINGO 13.0 software and ISP to get maximum profit.